(untitled) (Kinesiology, 2018)
The aim of this study was to verify whether the Nintendo Wii-Balance-Board was valid and reliable for assessing sit-to-stand and return-to-sit tasks by comparing it with a gold-standard force plate. Ten elderly (age = 78.21±14.82 years; males=4; females=6) and eleven young (age =24.25±12.43 years; males=6; females=5) participants of both genders performed five sit-to-stand and return-to-sit tasks consecutively by placing their feet on the Wii-Balance-Board; after two days of rest, they repeated the same assessment. The Wii-Balance- Board was positioned over the force plate to concurrently acquire the vertical component of ground reaction forces. Relevant kinetic and temporal parameters were estimated from these signals. Both the Wii-Balance-Board and force plate measurements resulted in a high level of correlation for almost all the parameters (Pearson’s product-moment r ranged from 0.91 to 0.99, p<.001) and, for the same parameters, intra-class correlation coefficients revealed a high level of agreement between the devices (ranged from 0.93 to 0.99). Bland-Altman plots and regression analysis detected systematic and fixed biases for two parameters (i.e., the inclination of force in standing and rising), while other parameters resulted with none systematic biases; the absolute magnitude of those differences was trivial or small (standardized biases ranged from 0.01 to 0.4). A high level of intra-device reliability was measured for all the parameters (intra-class correlation coefficients ranged from 0.85 to 0.99). The Wii-Balance-Board proved valid and reliable in comparison with a force plate for assessing transition movements so it can be considered a valuable solution for supporting the assessment procedures of average practitioners. Key words: sit-to-stand, return-to-sit, validity analysis, low-cost device, reliability analysis